MODERN VIEWS ABOUT THE PATHOPHYSIOLOGY OF ATHEROSCLEROSIS. PART 1. THE ROLE OF IMPAIRED LIPID METABOLISM AND ENDOTHELIAL DYSFUNCTION (LITERATURE REVIEW) - Алексей Михайлович Чаулин; Юлия Владимировна Григорьева; Дмитрий Викторович Дупляков (Медицина в Кузбассе, 2020)
According to modern concepts, atherosclerosis is a chronic inflammatory disease of the vascular wall, which is characterized by the accumulation (accumulation) of lipids, proliferation of vascular smooth muscle cells, apoptosis, cell necrosis, fibrosis and local inflammation. Numerous mechanisms are involved in the pathophysiology of atherosclerosis, among which a key role is played by: violation of lipid metabolism and modification of low-density lipoproteins, endothelial dysfunction, immune and inflammatory processes. There are complex and multi-component interactions between these mechanisms, which we discuss in this review.